Cellulose Hydrogels Containing Geraniol and Icaridin Encapsulated in Zein Nanoparticles for Arbovirus Control - Rogerio, Carolina B. [UNESP] (2022)
The most important arboviruses are those that cause dengue, yellow fever, chikungunya, and Zika, for which the main vector is the Aedes aegypti mosquito. The use of repellents is an important way to combat mosquito-borne pathogens. In this work, a safe method of protection employing a repellent was developed based on a slow release system composed of zein nanoparticles containing the active agents icaridin and geraniol incorporated in a cellulose gel matrix. Analyses were performed to characterize the nanoparticles and the gel formulation. The nanoparticles containing the repellents presented a hydrodynamic diameter of 229 ± 9 nm, polydispersity index of 0.38 ± 0.10, and zeta potential of +29.4 ± 0.8 mV. The efficiencies of encapsulation in the zein nanoparticles exceeded 85% for icaridin and 98% for geraniol. Rheological characterization of the gels containing nanoparticles and repellents showed that the viscoelastic characteristic of hydroxypropylmethylcellulose gel was preserved. Release tests demonstrated that the use of nanoparticles in combination with the gel matrix led to improved performance of the formulations. Atomic force microscopy analyses enabled visualization of the gel network containing the nanoparticles. Cytotoxicity assays using 3T3 and HaCaT cell cultures showed low toxicity profiles for the active agents and the nanoparticles. The results demonstrated the potential of these repellent systems to provide prolonged protection while decreasing toxicity.